2017
DOI: 10.7554/elife.24661
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction current is essential for stability of the transducing stereocilia in mammalian auditory hair cells

Abstract: Mechanotransducer channels at the tips of sensory stereocilia of inner ear hair cells are gated by the tension of 'tip links' interconnecting stereocilia. To ensure maximal sensitivity, tip links are tensioned at rest, resulting in a continuous influx of Ca2+ into the cell. Here, we show that this constitutive Ca2+ influx, usually considered as potentially deleterious for hair cells, is in fact essential for stereocilia stability. In the auditory hair cells of young postnatal mice and rats, a reduction in mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 58 publications
4
87
3
Order By: Relevance
“…A difference in Ca 2+ selectivity may be crucial: P Ca /P Cs = 1.8 for the anomalous PIEZO2 channels but P Ca /P Cs = 5 for the MT channel in OHCs . Ca 2+ influx through the hair cell channel is essential for generating adaptation, and has also been proposed to be necessary for regulating actin polymerization at the stereociliary tips and hair bundle organization (Velez-Ortega et al 2017). This requirement is presumably the reason that, in order to direct bundle maturation, cochlear hair cells acquire mechanotransducer channels early in development, well before the onset of hearing, which occurs around postnatal day 12 in mice.…”
Section: Resultsmentioning
confidence: 99%
“…A difference in Ca 2+ selectivity may be crucial: P Ca /P Cs = 1.8 for the anomalous PIEZO2 channels but P Ca /P Cs = 5 for the MT channel in OHCs . Ca 2+ influx through the hair cell channel is essential for generating adaptation, and has also been proposed to be necessary for regulating actin polymerization at the stereociliary tips and hair bundle organization (Velez-Ortega et al 2017). This requirement is presumably the reason that, in order to direct bundle maturation, cochlear hair cells acquire mechanotransducer channels early in development, well before the onset of hearing, which occurs around postnatal day 12 in mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that an abnormal shortening of mechanotransducing stereocilia has also been reported in mice deficient for several components of the mechano‐electrical transduction machinery, namely the TMC1/TMC2 channel complex (Kawashima et al , ), TMIE (Zhao et al , ), LHFPL5 (Xiong et al , ), and sans or cadherin‐23 (Caberlotto et al , ) and PCDH15 (Pepermans et al , ). Furthermore, Velez‐Ortega and colleagues recently showed that reducing mechano‐electrical transduction currents in wild‐type mouse or rat hair cells, using pharmacological channel blockers or disruption of tip links, leads to reduction in the height of the middle and shortest row “transducing” stereocilia (Velez‐Ortega et al , ). Thus, it is possible that the stereocilia phenotype observed in clarinet mutant mice is a downstream consequence of a defect in mechano‐electrical transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data point to a particular requirement for β-actin in maintaining stereocilia length. As with Actb knockout, blocking mechanotransduction also results in degeneration of the shorter rows of stereocilia, which can subsequently regrow when mechanotransduction is restored (29). Considering that the mechanotransductive apparatus is under constant mechanical stress, one possibility is that damage and repair during aging results in cycles of stereocilia shortening and regrowth (30).…”
Section: Discussionmentioning
confidence: 99%